The effect of problem-based STEM practices on pre-service science teachers' conceptual understanding - Seyyit Altunışık; Salih Uzun; Didem İnel Ekici (Journal of Pedagogical Research, 2023)
Problem-based STEM education can be defined as the solving of real-life problems by using science, technology, engineering, and mathematics disciplines. This study aims to determine the effect of problem-based STEM practices on pre-service teachers' conceptual understanding. The pre-service science teachers participated in 12 weeks of STEM activities that focused on problem-solving. The study comprises four problem-based STEM activities that are based on real-life problems. This study employed a quasi-experimental, one-group pretest-posttest design. The study sample consisted of twenty-seven pre-service science teachers in a science teacher program at a state university in Türkiye. The researchers developed four conceptual understanding tests, each consisting of four or five open-ended questions, as a data collection tool in the study. The data obtained were classified using predetermined categories (e.g., complete understanding, no understanding), and the differences in conceptual understanding between the pre- and post-tests were determined using the paired samples t-test. The results indicate that problem-based STEM practices can enhance the conceptual understanding of pre-service science teachers in science education.